A novel technique of rotator cuff repair using spinal needle and suture loop - Muzaffar Nasir; Yoon Jung-Ro; Kim Youngbae B (BMC, 2010)
Abstract Background We present a simple technique of arthroscopic rotator cuff repair using a spinal needle and suture loop. Methods With the arthroscope laterally, a spinal needle looped with PDS is inserted percutaneously into the shoulder posteriorly and penetrated through the healthy posterior cuff tear margin. Anteriorly, another spinal needle loaded with PDS is inserted percutaneously to engage the healthy tissue at the anterior tear margin. The suture in the anterior needle is then delivered into the suture loop of the posterior needle using a suture retriever. The posterior needle and loop are then pulled out carrying the anterior suture with it. The two limbs of this suture are then retrieved through a cannula for knotting. The same procedure is then repeated for additional suturing. Suture anchors placed over the greater tuberosity are used to complete the repair. Conclusion This is an easy method of rotator cuff repair using simple instruments and lesser time, hence can be employed at centers with less equipment and at reduced cost to the patient.